1992
DOI: 10.1007/bf02067011
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of deep vein thrombosis in patients with hip fractures: Low molecular weight heparin versus dextran

Abstract: A randomized open trial was undertaken to compare the antithrombotic efficacy of a low molecular weight heparin (LMWH; Sandoparin) with that of dextran 70 in patients undergoing surgery for hip fracture. One hundred thirteen patients received LMWH once daily subcutaneously at a fixed dosage while 103 patients received intravenous dextran 70. Postoperative deep vein thrombosis (DVT) was assessed by a diagnostic algorithm using the 125Iodine fibrinogen uptake test as screening and Duplex ultrasonography and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Dextran, however, was associated with a lower risk of major bleeding than heparins [4/1030 (0.4%) dextran versus 12/1206 (1.2%) heparin regimen; risk reduction 64% (32); 2p = 0.04 (Figure 30)]. Only eight 39,85,112,[117][118][119][120][121] of the 15 trials reported data on PE, and owing to the small numbers of patients included in such trials and the low event rate there was limited power to assess the relative effectiveness of the regimens for preventing PE [12/684 (1.8%) dextran versus 9/679 (1.3%) heparin; odds increase 31% (51), NS (Figure 31)]. …”
Section: Direct Comparison Of Dextran With a Heparin Regimenmentioning
confidence: 99%
“…Dextran, however, was associated with a lower risk of major bleeding than heparins [4/1030 (0.4%) dextran versus 12/1206 (1.2%) heparin regimen; risk reduction 64% (32); 2p = 0.04 (Figure 30)]. Only eight 39,85,112,[117][118][119][120][121] of the 15 trials reported data on PE, and owing to the small numbers of patients included in such trials and the low event rate there was limited power to assess the relative effectiveness of the regimens for preventing PE [12/684 (1.8%) dextran versus 9/679 (1.3%) heparin; odds increase 31% (51), NS (Figure 31)]. …”
Section: Direct Comparison Of Dextran With a Heparin Regimenmentioning
confidence: 99%
“…The RR calculated from each trial were combined using both Bayes (fixed-effects) and DerSi- Binsack et al [29] double blind, randomised insufficient patient, bleeding and DVT data Haas ct al. [35] open, randomised DVT diagnosed by FUT only, no bleeding information Hesset al [27] open, randomised double publication -also reported as Oertli et al [8] Lassen ct al. [28] double blind, randomised patients studied arc a subset of patients from the article by Lassen et al [ 12] Lcclercet al [30] double blind, randomised DVT not diagnosed in all cases by phlebography, insufficient bleeding information Matzsch et al [31] open, randomised no figures for DVT diagnosed by phlebography, insufficient bleeding information Gerhart et al [32] randomised, open label, prospective insufficient information regarding DVT diagnosis, combined treatment with both warfarin and LMWH after post-operative day 5.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] with 24 relevant treatment arms were included (table 1), and 9 studies [27][28][29][30][31][32][33][34][35] were excluded (table 2). Only 2 stud ies with 3 relevant treatment arms compared LMWH to warfarin.…”
Section: Literature Searchmentioning
confidence: 99%
“…Eight patients died during the study period. The (1)(2)(3)(4)(5)(6)(7)(8), but no study has been conducted with the aim of evaluating preoperative thromboprophylaxis. One study (8) applying preoperative phlebography proved 12% of patients developed DVT preoperatively.…”
mentioning
confidence: 99%